1996
DOI: 10.1007/s004380050115
|View full text |Cite
|
Sign up to set email alerts
|

RNA facilitates RecA-mediated DNA pairing and strand transfer between molecules bearing limited regions of homology

Abstract: The RecA protein of Escherichia coli catalyzes homologous pairing and strand exchange between a wide range of molecules showing nucleotide sequence complementarity, including a linear duplex and a single-stranded DNA molecule. We demonstrate that RecA can promote formation of joint molecules when the duplex contains an RNA/DNA hairpin and a single-stranded circle serves as the pairing partner. A chimeric RNA/DNA hairpin can be used to form stable joint molecules with as little as 15 bases of shared homology as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

1997
1997
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…The first model suggests that DPS1 and DPS2 regulate transcription of one or more RNAs that act in cis, spreading outward along the chromosome from their site of synthesis to enhance the recombinational potential of DNA with which they are associated. How such an RNA or RNAs would promote recombination is not known, although RNA as a recombination enhancer is not unprecedented (Kotani et al 1996;Yoon et al 1996). Several precedents exist for cis-acting RNAs that profoundly affect the behavior of the associated chromosome.…”
Section: Models For the Role Of ␣2p In Donor Preferencementioning
confidence: 99%
“…The first model suggests that DPS1 and DPS2 regulate transcription of one or more RNAs that act in cis, spreading outward along the chromosome from their site of synthesis to enhance the recombinational potential of DNA with which they are associated. How such an RNA or RNAs would promote recombination is not known, although RNA as a recombination enhancer is not unprecedented (Kotani et al 1996;Yoon et al 1996). Several precedents exist for cis-acting RNAs that profoundly affect the behavior of the associated chromosome.…”
Section: Models For the Role Of ␣2p In Donor Preferencementioning
confidence: 99%
“…RNA, a product of transcription, plays a role in extending the half-life of DNA molecules during the initial phase of recombination. They observed that the length of the complementary sequence required for stable DNA pairing might be reduced when one of the molecules contains RNA [21]. As DNA pairing is the rate-limiting step during homologous recombination, they tried to control this phase to improve the frequency of gene targeting.…”
Section: The Basis Of a Newly Developed Strategymentioning
confidence: 98%
“…131,132 The initial chimeraplast design was a contiguous stretch of 68 nucleotides containing both RNA and DNA residues (Fig. 5A).…”
Section: Gene Repair Strategiesmentioning
confidence: 99%